ALGUNAS CONSIDERACIONES ACERCA DEL PILATES. - Fente Cuesta, Lola (Medicina Naturista)
In this article I will try to answer the questions we ask ourselves when they talk to us about the Pilates method, because we have a friend or relative who practices it, who is hooked on the method and is feeling better, or his back pain disappeared and he don't want miss a class for nothing in the world.